DIFERENSIAL LEUKOSIT IKAN GURAMI (Osphronemus gouramy Lac.) DENGAN PERBEDAAN LEVEL SUPLEMENTASI Spirulina platensis DALAM PAKAN - Hikmah Widyaningrum; Sorta Basar Ida Simanjutak; Priyo Susatyo (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
The aim of this research was to know the effect of supplemented Spirulina platensis in diet on leukocytes differential of gourami (Osphronemous gouramy Lac.) and to obtain the best dose. This research was carried out experimentally using a completely randomized design (RAL), which consists of 4 treatments and 3 repetitions. The fish fed with diets which contain different levels of (0, 2.4, and 6g/kg) Spirulina platensis were investigated. Sampling was done 4 times at intervals of 2 weeks of the feeding experiment, leukocyte differential (monocyte, lymphocyte, neutrophil, eosinophyl) of blood taken from fish were determined. The results showed that the highest percentage of lymphocytes was found in level of supplementation of 4 g/kg of diets, whereas the highest percentage of monocytes, neutrophils and eosinophils were found at the level suplemetation 2 g/kg of diets. Level supplementation of S. platensis 4 g/kg of diets is an efficient and effective level in stimulating immune system cells of gourami, particularly lymphocytes cell.